"It's a tricky one" – development practitioners' attitudes towards religion. Issue 5 (3rd July 2020) - Khalaf-Elledge, Nora
ABSTRACT: Situated within post-colonial development critique, this article explores prevalent attitudes of development practitioners towards religion and their potential policy and practice impacts. The discussion draws on evidence from interviews and document analyses of government aid agencies, their recipient organisations, and local activists. The findings suggest that a lack of religious literacy, interest, and contact with religion has fostered an Orientalist mindset that essentialises religion as backwards, risky, and a unique feature of the "developing world". Contrary to global policy pushes, addressing religion in practice continues to be largely left to individual discretion and practitioners show an overwhelming reluctance to engage.